Capitalism, democracy, and welfare - Iversen, Torben (Cambridge studies in comparative politics, 2005)
This book, first published in 2005, builds on institutionalist theory in both economics and political science to offer a general political economy framework for the study of welfare capitalism. Based on the key idea that social protection in a modern economy, both inside and outside the state, can be understood as protection of specific investments in human capital, the book offers a systematic explanation of popular preferences for redistributive spending, the economic role of political parties and electoral systems, and labor market stratification (including gender inequality). Contrary to the popular idea that competition in the global economy undermines international differences in the level of social protection, the book argues that these differences are made possible by a high international division of labor. Such a division is what allows firms to specialize in production that requires an abundant supply of workers with specific skills, and hence high demand for protection